Effect of combination of vitamin-mineral supplementation and concentrate- to-roughage ratio diets on ruminal fermentation, gas kinetics and microbial biomass production using in vitro gas production technique - Poolthajit, Sukanya; Wachirapakorn, Chalong; Haitook, Theerachai; Srakaew, Wuttikorn; Prapaiwong, Tipwadee; Tongnum, Atichat (Agriculture and Natural Resources, 2021)
A vitamin-mineral combination consisting of betaine, biotin and chromium picolinate (BBC) was developed and the effects of BBC supplementation were investigated using an in vitro gas production technique. The effects were examined on the gas kinetics, microbial biomass production (MBP) and rumen fermentation. The experimental design was a 3×4 factorial arrangement in a completely randomized design. Factor A was the concentrate (C)-to-roughage (R) ratio of diets with three levels (50C:50R, 60C:40R, 70C:30R) and factor B was the amount of BBC supplementation with four levels (0 g/kg dry matter (DM); 3 g/kg DM; 6 g/kg DM; 9 g/kg DM). The gas production was recorded at 1 hr, 2 hr, 4 hr, 6 hr, 8 hr, 12 hr, 16 hr, 24 hr and 48 hr of incubation. The gas kinetics, truly digestible organic matter (TDOM), MBP and efficiency of MBP were measured. Ammonia nitrogen (NH3-N) and total volatile fatty acids (TVFA) were analyzed in fluid. The results revealed that the gas kinetics (a and b) did not differ among treatments, but the gas production rate constants (c) increased when the C:R ratio in diets increased (p < 0.05). TDOM, MBP and EMBP differed (p < 0.05) among treatments, and the C:R ratios influenced (p < 0.05) the extent of the difference, but the amount of BBC supplementation did not. The NH3-N concentration was greater (p < 0.05) in diets supplemented with BBC than in a diet without BBC supplementation. Increasing the C:R ratio in the diet resulted in lower acetic acid and higher propionic acid proportions (p < 0.01). In conclusion, increasing the C:R ratio from 50C:50R to 60C:40R or 70C:30R resulted in enhanced TDOM, MBP and TVFA. BBC inclusion had no positive effect.